Storm warning [compact disc, unabridged] - Park, Linda Sue (39 clues ;)
Amy and Dan Cahill hit the high seas as they follow the trail of some infamous ancestors to track down a long lost treasure. However, the real prize isn't hidden in a chest. It's the discovery of the Madrigals' most dangerous secret and, even more shockingly, the true identity of the mysterious man in black.